A Scoping Review of Recreational Sport Programs for Disabled Emerging Adults. Issue 1 (2nd January 2020) - Orr, Krystn; Evans, M. Blair; Tamminen, Katherine A.; Arbour-Nicitopoulos, Kelly P.
ABSTRACT: Purpose : Recreational sport programs are a critical but overlooked pathway for enhancing social participation of emerging adults with disabilities. Specifically, the experiences of recreational sport program members are important for continued community engagement among emerging adults. To address this gap, this scoping review examined the published studies on recreational sport programs for emerging adults with disabilities with the aim of providing future directions for practice (e.g., program instruction) and research (e.g., measurement). Method : Using the PRISMA-SR guidelines, six electronic databases were searched using key terms of disability, age, and recreational sport; findings were extracted and summarized according to the quality parasport participation framework (autonomy, belonging, challenge, engagement, mastery, meaning) and other outcome measures of the included studies. An online 26-item survey was sent to the included studies' authors to further explore the programs' conditions. Results : There were 16, 818 records screened with seven articles included. Studies indicate positive outcomes for emerging adults with disabilities immediately following participation in sport programs (e.g., improved self-esteem, autonomy, friendship skills, and balance). No longitudinal studies have been conducted on sustained participation in sport programs or transfer effects of participation. Conclusion : Despite the limited literature, this scoping review provides the foundation for the development of evidence-informed, participant-driven sport programs for emerging adults with disabilities. This study highlights areas for further development for both researches (e.g., evaluating and reporting quality) and practice (e.g., program evaluation).